IDENTIFYING CHANGES IN MANGROVE FOREST DISTRIBUTION IN LANGKAT REGENCY USING GOOGLE EARTH ENGINE - Rina Mawardah Batubara; M Taufik Rahmadi; Meilinda Suriani Harefa; Darwin Parlaungan Lubis; Sendi Permana; Rifqi Ulfatun Nikmah; Alvin Pratama (GeoEco, 2025)
Mapping the distribution of mangrove forests is very important to determine the ecological changes, because mangroves protect biodiversity. Google Earth Engine (GEE) is a cloud-based platform that can analyse the distribution of mangrove forests in a complex and efficient manner. This study aims to analyse the use of Google Earth Engine in monitoring changes in the distribution of mangrove forests in Langkat Regency from 2018 to 2024. This study uses Sentinel-2A image data by applying NDVI computed on Google Earth Engine (GEE). The results of the study show that there has been a change in the distribution of mangrove forests from 27,095.4 Ha (2018) to 26,700.56 Ha (2021) and to 24,685.74 Ha (2024), which shows a reduction in distribution by 394.84 Ha (2018-2021) and 2,014.82 Ha (2021-2024). The largest change in distribution occurred in Pangkalan Susu District with a reduction in area of 307.99 Ha (2021) and 984.64 Ha (2024). Changes in the distribution of mangrove forests are caused by human activities in land clearing for ponds and oil palm plantations. The accuracy test of the Sentinel-2A image uses a Confusion Matrix with an Overall Accuracy of 85%. This study shows the potential that Google Earth Engine-based Citra Sentinel-2A data can be used to monitor the distribution of mangrove forests.